Role of Housing Life-Support Technologies in the Development of Post-Urban Lifestyles - A. V. Ermishina; G. N. Donchevsky; L. V. Klimenko (Управление)
The paper is devoted to a concept study and empirical verification of the hypothesis about existence and development of new post-urban lifestyles in Russian society, which are formed on the basis of industrial and urban state of life, but trying to overcome the urbanism limitations. The authors differentiate posturban representatives as down-shifters and up-shifters. Materials of conducted empirical investigation have demonstrated that innovative technological solutions and modern autonomous eco-friendly housing lifesupport technologies take an important place in post-urban representatives’ socio-economic activity models.